2017
DOI: 10.4314/jasem.v20i4.30
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of crude oil polluted soil by applying single and combined cow-dung and hydrogen peroxide as remediating agents

Abstract: ABSTRACT:The study aimed at enhancing the remediationof crude oil polluted soil of the Niger Delta using cow dung and hydrogen peroxide in either single or combined forms. 5 kg of soil each was polluted with 200 ml of crude oil representing 4% w/v. Five amendment treatments labelledA-E were done in order of A (polluted soil + 1.2 kg cow dung), B (polluted soil + 1000 ml Hydrogen peroxide), C (polluted soil + 0.6 kg cow dung +500 ml hydrogen peroxide), D (polluted soil without amendment) and E (unpolluted soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
1
3
1
Order By: Relevance
“…This is also in agreement with the work of Onifade et al 34 , who observed the same trend of result when working on bioremediation of crude oil-polluted soil using enhanced natural attenuation. However, the result is in contrast with the work of Benson et al 32 . The increase in nitrogen observed in the cassava peel treated soil may be linked to nutrient supply from the cassava peel (organic waste) which improved soil properties and subsequently its fertility.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…This is also in agreement with the work of Onifade et al 34 , who observed the same trend of result when working on bioremediation of crude oil-polluted soil using enhanced natural attenuation. However, the result is in contrast with the work of Benson et al 32 . The increase in nitrogen observed in the cassava peel treated soil may be linked to nutrient supply from the cassava peel (organic waste) which improved soil properties and subsequently its fertility.…”
Section: Discussioncontrasting
confidence: 98%
“…The pH values of crude oil polluted soil were lower as compared to the unpolluted soil (double control) at 0 months, a finding which is in line with Benson et al 32 . The increase in pH values (decrease in acidity) may be due to the increased degradation of crude oil by microorganisms in the soil.…”
Section: Discussionsupporting
confidence: 88%
“…Many studies have reported the use of oilfield wastewater as nutrient supplement [11,12,13]. Benson et al [14] reported decrease in nitrate content of amended soil and increase in un-amended soil. Onuh et al [15] also observed a decrease in nitrogen availability with increased levels of crude pollution.…”
Section: Discussionmentioning
confidence: 99%
“…Accidental spills and leakages that occur during the exploration, refining, transportation and storage of petroleum and its products affect the environment 1 . It causes physical, chemical and biological damage to the affected environment (land, water and air) thus soil contamination with petroleum compounds is of great concern worldwide.…”
Section: Introductionmentioning
confidence: 99%